Regional disparities in suicide among patients with cancer: A nationwide population‐based study in Japan - Ken Kurisu; Saki Harashima; Maiko Fujimori; Tatsuo Akechi; Kazuhiro Yoshiuchi; Yosuke Uchitomi (Cancer Medicine, 2023)
Abstract Background This study aimed to explore prefecture‐level differences in suicide risk among patients with cancer in Japan. Methods Data from the National Cancer Registry, which covers the entire Japanese population, were used. Patients diagnosed with cancer between 2016 and 2017 were included. The standardized mortality ratio (SMR) for suicide within 2 years after cancer diagnosis was quantified compared with the general population for each prefecture. Multivariate Poisson regression analysis was conducted to quantify the adjusted relative risk using Hokkaido as the reference. Results The analysis included 2,133,502 patients. The SMRs were high among patients with cancer residing in certain prefectures, such as the Hokuriku region (the middle and western parts of Japan's main island). These areas also exhibited a significant relative risk in the Poisson regression model. Conclusion The results demonstrated that patients with cancer in certain prefectures in Japan have a high suicide risk.